ANALYSIS OF FACTORS ASSOCIATED WITH STUDENT PARTICIPATION IN THE FREE HEALTH CHECK PROGRAM AT SENIOR HIGH SCHOOLS IN BARANTI DISTRICT SIDENRENG RAPPANG REGENCY - Adriyani; Zulkarnain Sulaiman; Khaeriyah Adri; Nurjannah Nonci (JTH: Journal of Technology and Health, 2026)
The Free Health Check Program (CKG) is a school-based preventive health initiative intended to support early detection and strengthen adolescents’ health awareness. Participation, however, was incomplete at two senior high schools in Baranti District. This study analyzed the associations of knowledge, attitude, teacher support, implementation timing, and program implementation with student participation. An observational analytic study with a cross-sectional design was conducted among 83 students selected through stratified random sampling from SMAN 10 Sidenreng Rappang and MAN Sidenreng Rappang. Data were collected using a structured questionnaire that had demonstrated validity and reliability and were analyzed using the Chi-square test at α = 0.05. Of the respondents, 47 (56.6%) participated in the program. Knowledge (p < 0.001), teacher support (p = 0.041), implementation timing (p = 0.005), and program implementation (p = 0.001) were significantly associated with participation, whereas attitude was not (p = 0.398). These findings indicate that participation is associated with cognitive, reinforcing, and enabling factors. Schools and health services should strengthen pre-program health education, actively involve teachers, schedule activities to avoid academic conflicts, and improve service organization. Because the design was cross-sectional, the results indicate associations rather than causal relationships.